Analisis Vegetasi Mangrove di Pulau Liki, Distrik Sarmi Kota Kabupaten Sarmi - Rosye H.R. Tanjung; Agnes Kabelen; Alfred Antoh (Jurusan Biologi FMIPA Universitas Cenderawasih, 2015)
Utilization of mangrove forest is very important for people who are on the island of Liki. This study aims to determine the species composition of mangrove, mangrove vegetation structure and ecological values in the Liki Island District of Sarmi Kota, Sarmi Regency, Papua Province. The method used in this research is the transect method, by observation, interviews, documentation and literature review. The results of the study and analysis of the data showed the discovery of the species composition as much as 5 species of 3 families with a density of 105 individuals/ha at tree level, 5 species of 3 families with a density of 124 individuals/ha at the level of the pole, 5 species of 3 families with a density of 149 people/ha at stake levels and 5 types of 3 families with a density of 109 individuals/ha at the seedling stage. The index value of the highest importance that kind of Bruguiera sexangula 78.02% at tree level. Mangrove species diversity at the level of the tree, sapling and seedling were low with H'<2.5. This research concludes that: 1). the composition of mangrove on Liki island consist of 5 species of 2). the low regeneration of mangroves causes the amount of density, frequency and dominance are relatively low; 3). need to increase the awareness of the public about the importance of the island of Liki themselves in maintaining the stability of mangrove land and sea conditions.Key words: vegetation analysis, mangrove species, Liki Island, Sarmi, Papua.